Please: Use "^" to denote exponentiation: <span>2x^2 + 8x - 12 = 0
Reduce this by div. every term by 2: </span><span>x^2 + 4x - 6 = 0
Here a=1, b=4 and c = -6. Square half of b, obtaining (4/2)^2 = 4, and add, and then subtract, this 4 to x^2 + 4x - 6:
</span> x^2 + 4x +4 - 4 - 6 = 0. Rewrite the square as (x+2)^2, obtaining new equation
(x+2)^2 = 10. Take the sqrt of both sides: x+2 = plus or minus sqrt(10).
Finally, solve for x: x = -2 plus or minus sqrt(10).
Answer: x = 1 + 0.5c
Step-by-step explanation:
Answer:
because they made a mistake
Replace each occurrence of x by 7. So we have:-
7^2 + 3 / 7 - 9
= 52 / -2
= -26 answer